Factors Influencing Teacher Readiness in Implementing Authentic Assessment of Merdeka Belajar Curriculum - Naufalin, Lina Rifda; Anggraeni, Ade Irma; Krisnaresanti, Aldila; Janah, Miftahul (Dinamika Pendidikan, 2023)
This research aims to provide a factual analysis of the extent to which teachers are ready to apply the Merdeka Belajar Curriculum in terms of authentic assessment. Descriptive statistical analysis is a data analysis technique that uses software SmartPLS-based partial least squares (PLS-SEM). The population of this study was high school or equivalent teachers in Banyumas Regency, with 55 samples using the convenience sampling technique. As a result of research and discussion, it can be concluded that there is an influence from understanding the concept of authentic assessment and the ability to determine essential learning aspects to be assessed. Deciding which learning is crucial to assess also influences the ability to design assessment instruments. Meanwhile, the ability to design assessment instruments impacts the ability to prepare assessment documents, and the skills in administering assessment documents also influence the ability to analyze assessment results. The researchers recommend that schools continue to assist teachers in this regard and provide them with as much training as possible on the use of authentic assessment instruments in light of their findings.